Towards sustainable diagnostics: assessing biodegradable lateral flow cassettes in real world conditions in Africa - Oladipo, Elijah Kolawole; Brus, Sander Julian; Ogunmodede, Sola Peter; Barrios, Luis Fernando; Adigun, Gladys Ayodele; Popoola, Possible Okikiola (Frontiers in Lab on a Chip Technologies, 2026)
IntroductionThe widespread use of Lateral Flow Assays (LFAs) has significantly improved diagnostic accessibility in low- and middle-income regions, yet their reliance on single-use plastic cassettes poses urgent environmental concerns as conventional plastics persist for centuries, degrading only into harmful microplastics.MethodsThis study evaluated the biodegradability of certified plant-based diagnostic cassettes developed by Okos Diagnostics under field conditions in Nigeria using a 4-month controlled burial study across three soil types: sandy, clayey, and loamy. The biodegradable cassettes, made from certified plant-based polymers, were monitored using precision weight analysis and qualitative degradation assessments, compared against conventional plastic controls.ResultsResults demonstrated statistically significant degradation in biodegradable cassettes with weight increases of 7.44% ± 0.12% (sandy), 7.02% ± 0.08% (clayey), and 11.36% ± 0.16% (loamy soil), which showed the highest degradation rate. Observed initial weight increases primarily reflect moisture uptake and microbial biofilm formation on cassette surfaces rather than net polymer mass gain; these early-stage changes precede fragmentation and mineralization during biodegradation. ANOVA analysis revealed significant differences between soil types (F=15.7, p < 0.001) and materials (F=89.3, p < 0.0001), while plastic controls showed negligible change (1.36% ± 0.04%). Posthoc Tukey analysis showed that degradation in loamy soil was significantly higher than in sandy and clayey soils (p < 0.05).DiscussionThe study validates biodegradable cassettes as eco-friendly alternatives capable of reducing diagnostic waste in resource-limited settings and provides baseline biodegradation data for tropical environments to inform global standards on sustainable diagnostic materials.